‘Kiremt’ 2024 National Climate Outlook Forum (NCOF): ‘Belg’ 2024 Impact Assessment and ‘Kiremt’ 2024 Impact Outlook - Teshome, Asaminew; Kebede, Bekele; Tamene, Bekalu; Muluneh, Mihret; Ambaw, Gebermedihin (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The National Climate Outlook Forum (NCOF) recently convened to assess the Belg 2024 season and provide an outlook for the Kiremt 2024 season. Organized by the Ethiopian Meteorological Institute (EMI) in collaboration with AICCRA, the Ministry of Water and Energy (MoWE), and the World Meteorological Organization (WMO), the forum serves as a crucial platform for collaboration among decision-makers, climate scientists, researchers, media, climate information users, and development partners. Its primary goal is to co-design, co-produce, and co-own climate services, thereby enhancing societal resilience to climate variability and extreme weather events. Seasonal forecasts are essential for decision-making in sectors such as agriculture, water resource management, energy planning, and disaster preparedness. By predicting temperature and precipitation patterns over specific periods, these forecasts enable stakeholders to proactively plan for risks and opportunities associated with seasonal changes. The NCOF facilitates reviewing past climate performance, verifying forecasts, addressing user feedback, and communicating future outlooks. The workshop comprised three sessions, beginning with opening remarks by Mr. Fetene Teshome, General Director of EMI, followed by keynote speeches and technical presentations. The first session involved detailed reviews and impact assessments of the Belg 2024 forecast across various sectors. The second session examined forecasts and anticipated impacts of the upcoming Kiremt 2024 season in agriculture, water, health, and disaster risk management. Key objectives of the workshop included fostering stakeholder engagement in the co-production of climate assessments and outlooks at national and regional levels. 340 (110 of which are women) stakeholders participated in the event, underscoring the collaborative effort to enhance climate service delivery and preparedness across Ethiopia.